Cognitive behavior therapy for OCD in youth : a step-by-step guide - Tompkins, Michael A. (American Psychological Association, 2020)
"Obsessive compulsive disorder (OCD), which can cause significant impairment in personal, social, and academic contexts, affects nearly half a million children in the United States. This step by step guide provides mental health professionals with an adaptable, evidence based model that uses cognitive behavior therapy to treat pediatric OCD. The authors present well tested, empirically validated strategies that encourage clinical flexibility and creativity. Chapters describe the nuts and bolts of assessment, case conceptualization, and treatment planning, as well as psychoeducation, pharmacotherapy, strategies for relapse prevention, and involving family members in treatment. Richly described case studies illustrate how core strategies can be effectively implemented with youth between the ages of 7 and 18. Includes downloadable handouts for clinical use, including worksheets and fact sheets for parents and guardians, exercises and games, and other clinical tools and resources"--